Pengaruh Metode Latihan Plyometric dan Latihan Beban dengan Kecepatan Reaksi terhadap Power Otot Tungkai Pemain Bolavoli Putra - Supriyanto Supriyanto (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2018)
The purpose of this study was to know the effect of plyometric training and weight training with reaction speed toward limb muscle of male volleyball players. The method of the study was treatment design level 2 x 2 , where the independent variable was classified in two parts. The findings were: (1) overall, there is different significant effect of plyometric training and weight training toward limb muscle power of volleyball players (Fh = 0.58 <Ft = 4.00), (2) there is interaction between training methods and reaction speed toward limb muscle power of male volleyball players of SMA IQRO IT Bengkulu city (Fh = 28.39> Ft = 3.97), (3) volleyball players who have high speed reaction have better limb muscle power if using training method rather than training with the Plyometric training method (Fh = 5.35> Ft = 4.01). (4) Volleyball players who have low reaction speed have better limb muscle power if trained by weight training method (fh = 5.12> ft = 4.01). In Conclusion, volleyball players who have high reaction speed are more efficient trained by weight training, meanwhile volleyball players who have low reaction speed are more efficient trained by plyometric training Keyword: Plyometric Exercise Method, Reaction Speed, Power of Leg Muscles.